Effects of Organic Amendments on Soil Aggregate Stability, Carbon Sequestration, and Energy Use Efficiency in Wetland Paddy Cultivation - Mohammad Mizanur Rahman (Sustainability, 2022)
A study was conducted to assess the effects of organic amendments on soil aggregates, carbon (C) sequestration, and energy use efficiency (EUE) during five consecutive Boro and Transplanted Aman rice seasons in Bangladesh during 2018–2020. Five treatments (viz., control (only inorganic fertilizers), cow dung (CD), vermicompost (VC), rice straw (RS), and poultry manure (PM)) were used. The organic materials were applied at 2 t C ha−1 season−1 to all the plots, except in the control treatment. Inorganic fertilizers were applied in all treatments in both seasons following integrated nutrient management (INM). The data reveal that PM was found to be more efficient at increasing the water-stable soil aggregates (WSA), followed by the RS, CD, and VC. The WSA in smaller-sized soil aggregates were found to be higher than those in larger-sized soil aggregates. VC was found to be the most effective in terms of C sequestration (29%), followed by PM (26%), CD (22%), and RS (20%). The highest EUE was attributed to the control treatment (9.77), followed by the CD (8.67), VC (8.04), RS (2.10), and PM (1.18), which showed energy wastage in the organic treatments. The system productivity (SP) followed the opposite trend of the EUE. The INM is a better approach to improve the soil health, the C sequestration, and the SP, but it appeared as an energy-inefficient strategy, which suggests that a balanced application of organic and inorganic nutrients is needed in order to achieve yield sustainability and EUE.